Tourism Village Strategic Marketing Plan Model in Bondowoso - Firman Restu Hikmatullah; Ika Barokah Suryaningsih; Nurhayati Nurhayati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to explore the condition of tourist villages in Bondowoso Regency, explore government policies related to the management and development of tourist villages in Bondowoso Regency and formulate a strategic marketing plan model for tourist villages in Bondowoso Regency. This research is a qualitative descriptive study with a case study approach by exploring a condition, namely a tourist village in the Bondowoso Regency area in detail, accompanied by extracting data from informants who understand the situation. The data analysis method in this study consisted of data collection (data collection), data reduction (data reduction), data presentation (data display) and conclusions (conclusions).